2022
DOI: 10.3390/biomedicines10102482
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Partial EMT and Cisplatin Resistance as the Drivers for Recurrence in HNSCC

Abstract: This study aims to investigate the role of partial epithelial to mesenchymal transition (pEMT)-related proteins in modulating Cisplatin resistance in head and neck squamous cell carcinoma (HNSCC). SCC-25 cells were pre-treated with TGF-beta1 followed by transient Krüppel-like Factor 4 (KLF4)-overexpression and Cisplatin treatment. Cell growth, cell morphological changes and cell migration were assessed using Juli BR live cell video-microscopy. In addition, Ki-67 and Slug immunostaining and follow-up image cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Chen et al 50 found that the interaction between CCL21 and CCR7 could significantly promote EMT process and tumor stemness of HNSC cells through JAK2/STAT3 signaling. Ingruber et al 51 discovered that the interaction between EMT and cisplatin resistance could act as a driver of HNSC recurrence. Yu et al 52 found that the IGF2BP2, a m6A reader, could promote the lymphatic metastasis and MET process of HNSC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al 50 found that the interaction between CCL21 and CCR7 could significantly promote EMT process and tumor stemness of HNSC cells through JAK2/STAT3 signaling. Ingruber et al 51 discovered that the interaction between EMT and cisplatin resistance could act as a driver of HNSC recurrence. Yu et al 52 found that the IGF2BP2, a m6A reader, could promote the lymphatic metastasis and MET process of HNSC.…”
Section: Discussionmentioning
confidence: 99%
“…Ingruber et al 51 discovered that the interaction between EMT and cisplatin resistance could act as a driver of HNSC recurrence. Yu et al 52 found that the IGF2BP2, a m6A reader, could promote the lymphatic metastasis and MET process of HNSC.…”
Section: Discussionmentioning
confidence: 99%
“…With the simultaneous use of differently labeled antibodies, multiplex cytometry is possible, allowing a differentiated analysis of the phenotype, spatial distribution, and activation of cells ( 24 ) in the TME. Recent imaging cytometric techniques allow automatic differentiation between tumor cell aggregates and tumor stroma in HNSCC ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Poor survival can be attributed to the high frequency of recurrence and second primary tumor, to tumor metastasis and radiochemotherapy (RCT) resistance [1,2]. Hypoxic conditions, cellular stress, mitochondrial dysfunction [3], and, in particular, the reversible process of partial epithelial to mesenchymal transition (pEMT) precondition tumor cells to therapy resistance [4][5][6]. Both applied RCT and pEMT processes might activate and stabilize the pro-EMT-transcription factor Slug and induce and sustain p38 mitogen-activated protein kinase (MAPK) phosphorylation [4].…”
Section: Introductionmentioning
confidence: 99%
“…During pEMT, polarized and differentiated epithelial cells acquire a reversible mesenchymal phenotype [6]; they underlie changes in morphology and give up their epithelial features and gene expression profile [7,8]. Cells undergoing pEMT release their lateral cell-cell contacts, their connection to the basal substrate, become motile, achieve collective invasion [4,6], and enforce stronger interaction with the extracellular matrix. These are typical features of the nonpolar mesenchymal phenotype [9].…”
Section: Introductionmentioning
confidence: 99%